PERAN MOTIVASI KERJA DAN KOMUNIKASI KERJA TERHADAP KINERJA PEGAWAI - Elli Asmawati; Sofia Ulfa Eka Hadiyanti; Yulia Tri Kusumawati (Universitas Sarjanawiyata Tamansiswa, 2026)
Employee performance is an important indicator of organizational effectiveness, particularly in public sector institutions that rely on human resources to support administrative services and digital governance. Work motivation and organizational communication are considered key factors that can influence employee performance. This study aims to analyze the effect of work motivation and work communication on employee performance at the Department of Communication and Informatics of East Kalimantan Province. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 94 employees selected using simple random sampling from a population of 123 employees. Data analysis was conducted using multiple linear regression with the assistance of SPSS. The results show that work motivation has a significant effect on employee performance (Sig. = 0.035). Work communication also has a significant effect on employee performance (Sig. = 0.038). Furthermore, work motivation and work communication simultaneously have a significant influence on employee performance. These findings indicate that strengthening employee motivation and improving communication within the organization play an important role in enhancing employee performance in government institutions. Keyword : Work Motivation, Work Communication, Employee Performance, Public Organization